Critical Care Nutrition in Nepal: Where do we stand? - Khanal, Sushil; Upadhyaya, Sarobar; Neupane, Ashesh; Acharya, Subhash Prasad (Journal of Nepalese Society of Critical Care Medicine, 2023)
Critical care nutrition is a vastly unexplored domain when it comes to managing critically ill patients admitted to the hospitals in Nepal. Patients who are critically ill require a holistic approach in their management and as such the nutritional part of their care cannot be overstated. The lack of regulatory bodies and practice guideline has been a long-standing problem. It is high time for nutrition to come to the forefront in a clinical scenario and play an equal part when it comes to treating critically ill patients, as they are more likely to be undernourished.